Oxidação cíclica de aços inoxidáveis ferríticos e duplex para fabricação de silenciosos de automóveis - Daniel de Rezende Silva (2018)
Automotive exhaust systems have components in relatively cold temperatures where the stainless steels used are subjected to direct contact with condensates of the combustion product of the fuels used, undergoing oxidative and corrosive processes. The objective of this work was to simulate the oxidative and corrosive processes that occur in the automotive muffler when subjected to the condensate from the combustion of automotive gasoline in four different stainless steels, AISI 409, AISI 439, AISI 444 and AISI 398 steels, evaluating the cyclic oxidation resistance of steels. The oxides formed after 500, 1000 and 1500 hours of Dip Dry test were Fe2O3, Fe3O4, Cr2O3, TiO2 and the Mn2TiO4 spinel for the AISI 409, 439 and 444 ferritic steels. The AISI 398 duplex steel produced Fe2O3, Fe3O4, Cr2O3, besides the Fe2MnO4 and Cr2FeO4 spinels. In the oxidized layer of the AISI 439, 444 and 398 steels, the presence of FeOCl from the reaction of the steel with the condensate was identified. FeOCl was not identified on the surface of 409 steel because of the spalling of the superficial oxide layer. The AISI 409 showed the lowest resistance to cyclic oxidation evaluated by the Dip Dry test and the AISI 398 showed the highest resistance to the Dip Dry test in synthetic gasoline condensate. The mass losses of the steels were 14% for the AISI 409 steel, 0.68% for steel 439 and 0.18% for AISI 444 steel and 0.10% for steel 398. Maximum thickness variations of less than 1% were obtained for AISI 439 steels, 444 and 398 and a thickness variation of 7% was obtained for AISI 409 steel after 1500 hours of Dip Dry test. The surface roughness of the 409 steel increased from 0.43 to 18.00 μm after 1500 hours of Dip Dry, while the roughness increase for the 398 steel was 0.66 μm after 1500 hours of Dip Dry. The AISI 409 steel had the lowest brightness from the initial state and, after the Dip Dry test of 500, 1000 and 1500 hours, lost almost all the brightness in the 60 degree angulation due to the higher degree of oxidation. The duplex steel was the least oxidized having the highest brightness after 1500 hours of cyclic oxidation test. AISI 439 and 444 steels had similar behavior, showing a brightness between 50 and 100 GU after the Dip Dry test. Prior to the Dip Dry test, AISI 398 steel was the most resistant to electrochemical corrosion in synthetic gasoline condensate and 409 steel was the least resistant. After 1000 h and 1500 h of Dip Dry test, the less noble AISI 409 and 439 steels were the most resistant to corrosion in gasoline condensate and the 444 and 398 steels were the least corrosion resistant. This result was obtained due to the higher oxidation of AISI 409 and 439 steels in the Dip Dry test, producing a protective oxide layer. The results of Mott Shottky indicated that defect density was reduced after 1500 hours of Dip Dry test for AISI 409 steel, which agrees with the polarization and impedance results indicating increased corrosion resistance of 409 steel after the test of Dip Dry by the formation of a more protective layer of oxides.